Biological and pharmaceutical nanomaterials - Kumar, Challa ; Ed (Wiley-VCH, 2006)
This first comprehensive yet concise overview of all important classes of biological and pharmaceutical nanomaterials presents in one volume the different kinds of natural biological compounds that form nanomaterials or that may be used to purposefully create them.